INFLUENCE OF MANAGERIAL ABILITY OF MADRASAH HEAD AND COMMITMENT TO TEACHER PERFORMANCE AT MAS PAB 02 HELVETIA - Syafaruddin Siahaan; Inom Nasution; Yayi Setia Ningrum (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
In general, this study aims to determine 1) the effect of managerial ability of madrasah principals on teacher performance at MAS PAB 02 Helvetia, 2) the effect of duty commitment of madrasah principals on teacher performance in MAS PAB 02 Helvetia, 3) the influence of managerial abilities of madrasah principals and task commitment. on teacher performance at MAS PAB 02 Helvetia. The managerial ability of madrasah principals is in the highest score of 6 people at 15%, moderate scores are 21 people at 52.5%, and low scores are 13 people at 32.5%. The distribution of task commitment scores is in the highest score, amounting to 18 people at 45%, moderate scores amounting to 18 people at 45%, and low scores amounting to 4 people at 10%. And for teacher performance in the highest score amounted to 13 people at 32.5%, moderate scores amounted to 20 people by 50%, and low scores amounted to 7 people by 17.5%. The managerial ability of madrasah principals has an influence on teacher performance with a coefficient of 0.242 and through the t test that has been carried out, it is obtained t count = 2.293 while the value of t table = 2.026. By obtaining tcount> ttable, it shows that the relationship between them is positive and significant. The commitment of the madrasah principal also has an influence on teacher performance with a coefficient of 0.395 and through the t test that has been carried out, it is obtained t count = 3.689 while t table = 2.026. By obtaining tcount> ttable, it shows that the relationship between them is positive and significant. And simultaneous testing was carried out in order to obtain the calculated F value of 9.405> 3.24 and the F significance value of 0.000 <0.05. In order to obtain a significance value of F <0.05, the effect of the managerial ability of the madrasah principal and task commitment on teacher performance at MAS PAB 02 Helvetia is acceptable (significant).